2021
DOI: 10.5195/jmla.2021.1165
|View full text |Cite
|
Sign up to set email alerts
|

A health literacy analysis of the consumer-oriented COVID-19 information produced by ten state health departments

Abstract: Objective: The COVID-19 pandemic highlights the public’s need for quality health information that is understandable. This study aimed to identify (1) the extent to which COVID-19 messaging by state public health departments is understandable, actionable, and clear; (2) whether materials produced by public health departments are easily readable; (3) relationships between material type and understandability, actionability, clarity, and reading grade level; and (4) potential strategies to improve public health me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
2
11
0
1
Order By: Relevance
“… 14 In their review of US state health department COVID-19 resources (e.g., webpages, infographics, and videos), Mani et al found information to have high understandability and actionability, while needing improvement in terms of overall clarity and readability. 15 …”
Section: Introductionmentioning
confidence: 99%
“… 14 In their review of US state health department COVID-19 resources (e.g., webpages, infographics, and videos), Mani et al found information to have high understandability and actionability, while needing improvement in terms of overall clarity and readability. 15 …”
Section: Introductionmentioning
confidence: 99%
“…The first peak relates to the first wave of the pandemic, the second peak to newly available vaccines, and the third peak to a significant COVID-19 wave in the province of Alberta along with COVID-19 booster vaccine availability. While other papers have reviewed the quality of COVID online information, their use has not been well described [8,9]. It can be inferred the target audience of Albertans was successfully reached, with a majority of use being from this geographic location, and significantly higher than other webpages on the site.…”
Section: Discussionmentioning
confidence: 99%
“…K. Patel et al, 2015;Vishnevetsky et al, 2018). This criterion was evaluated in 23 studies (Abdul Rahman et al, 2020;Alshehri & Joury, 2019;Alwani et al, 2021;Arslan et al, 2020;Bacher et al, 2020;Balakrishnan, Chandy, Hseih, et al, 2016;Bui et al, 2018;Edmunds et al, 2014;Georgsson & Carlsson, 2022;Gillum, 2017;Guitton, 2015;Gulbrandsen et al, 2022;Harris et al, 2018;Hughes et al, 2019;Lake et al, 2007;Lamb et al, 2022;Lipari et al, 2019;Mac et al, 2020;Magrath et al, 2022;Mani et al, 2021;McClure et al, 2016;Miles et al, 2021;O'Sullivan et al, 2020;Sideris et al, 2021;Townsend, 2011;Unaka et al, 2017;van Ballegooie & Hoang, 2021;Vishnevetsky et al, 2018;Wang et al, 2022).…”
Section: Comprehensibility or Comprehensionunclassified